2012
DOI: 10.1111/bjh.12008
|View full text |Cite
|
Sign up to set email alerts
|

Single‐agent lenalidomide in relapsed/refractory mantle cell lymphoma: results from a UK phase II study suggest activity and possible gender differences

Abstract: SummaryWe present data from a phase II study investigating a novel treatment strategy for relapsed/refractory mantle cell lymphoma (MCL). Twenty-six patients received lenalidomide 25 mg/d (days 1-21 of a 28-d cycle) for up to 6 cycles followed by low-dose maintenance lenalidomide (15 mg) in responding patients. Eight patients achieved complete or partial response to give an overall response rate of 31% with median response duration of 22Á2 months [95% confidence interval (CI) 0Á0-53Á6] and median progression-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 44 publications
5
50
0
Order By: Relevance
“…Responses to rituximab in patients with apparent progression of disease on lenalidomide alone were also observed. Finally, our ORR to single-agent lenalidomide, which was assessed at 2 months, is similar to the reported results for lenalidomide monotherapy in relapsed/refractory indolent non-Hodgkin lymphoma and MCL (10,(22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 87%
“…Responses to rituximab in patients with apparent progression of disease on lenalidomide alone were also observed. Finally, our ORR to single-agent lenalidomide, which was assessed at 2 months, is similar to the reported results for lenalidomide monotherapy in relapsed/refractory indolent non-Hodgkin lymphoma and MCL (10,(22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 87%
“…This immunomodulatory compound showed high antilymphoma activity in several other studies [39][40][41]. The ORR were around 30-50%, with promising CR rates up to 20% and PFS generally around 6-9 months.…”
Section: Immunomodulatory Drugsmentioning
confidence: 74%
“…26 Eve et al treated 26 relapsed/ refractory MCL cases with maintenance lenalidomide in responding patients to lenalidomide induction (Table 1). 29 In NHL-003, 57 relapsed/refractory MCL patients had an ORR of 42%. 47 Collectively, adverse effects (AEs) were primarily hematologic, with 5% of patients having thromboembolic events.…”
Section: -46mentioning
confidence: 99%
“…Clinical studies have examined potential biomarkers of lenalidomide efficacy, 28,29,34 and pivotal studies are ongoing in distinct NHL subsets (eg, non-GC DLBCL). In relapsed/refractory MCL, Zaja et al showed that microvessel density, macrophage, and NK cell counts were altered with lenalidomide, 28 and Ki67 is being studied as a biomarker.…”
Section: Future Directions Biomarkersmentioning
confidence: 99%